EVALUATION OF Salmonella sp CONTAMINATION AND ITS ANTIBIOTICS RESISTANCE PATTERNS ISOLATED FROM BROILER MEAT SOLD AT WET MARKET IN CENTER OF SURABAYA - Aprillian, Risky; Rahardjo, Dadik; Koesdarto, Setiawan (Indonesian Journal of Tropical and Infectious Disease, 2015)
Antibiotic resistance now days become a main issue to the medical researches as found many positive result of antibiotic resistance test. One of the causes of antibiotic resistance is using antibiotic as a feed additive to animal. Bacteria that are resistant to antibiotics can be a danger to humans, in this case the resistant bacteria as a result of treatment errors animals, especially chickens that uses low-dose antibiotics as growth promoters. This study aimed to determine the contamination of Salmonella sp and its antibiotics resistance patterns of Salmonella sp isolated from broiler meat sold at wet market in the Center of Surabaya: (a) Pasar Kembang, (b) Pasar Kupang, (c) Pasar Dukuh Kupang, (d) Pasar Kedungsari, (e) Pasar Kedungdoro and (f) Pasar Keputran. The method that used in this study was bacteriological isolation and identification method. The method started with pre-enrichment using Buffered Pepton Water, selective enrichment using Tetrathionate Broth and Selenite Cysteine broth, selective media using Salmonella-Shigella Agar, Biochemical test using Triple Sugar Iron Agar, Simon Citrate, Methyl Red – Voges Proskauer, and Sulfide Indol Motility, and followed with susceptibility test according to Kirby-Bauer method using Mueller-Hinton Agar. The antibiotics that used in susceptibility test were: (a) Meropenem, (b) Ampicillin Sulbactam, (c) Amikacin, (d) Ofloxacin and (e) Nalidixic Acid. The results of this study were found 90% or 27 of 30 samples positive contaminated with Salmonella sp. The results of antibiotics resistance from 27 isolates 0% were resistant to Meropenem, 0% were resistant to Amikacin; 3.7% were resistant to Ampicillin-Sulbactam; 11.1% were resistant to Ofloxacin and 44.4% were resistant to Nalidixic Acid.